The Influence of Sales Promotion on Social Media, E-WOM, and Brand Awareness on Purchase Decisions for Jade Perfume in Sidoarjo. - Rama Adhitya Erafasa1; Endah Budiarti , (International Conference On Economics Business Management And Accounting (ICOEMA), 2025)
Jade Parfum is an MSME engaged in the perfume sector, founded by a young entrepreneur who has a great interest in collecting and using various local perfume brands. In the midst of today's fierce business competition, social media has become an important tool for promoting products. This study aims to examine the effect of sales promotion on social media, E-WOM (electronic word of mouth), and brand awareness on purchasing decisions of Jade Parfum customers in Sidoarjo. The research method used is a quantitative approach with data collection through a questionnaire, which is then analyzed using multiple linear regression. Hypothesis testing is done using the T test, F test, and the coefficient of determination (R²). The analysis results show that all indicators used are valid and reliable. The T test reveals that sales promotion, E-WOM, and brand awareness have a significant influence on purchasing decisions. The F test shows that the three variables simultaneously have a significant influence on purchasing decisions for Jade Parfum in Sidoarjo. The coefficient of determination (R²) indicates that the independent variable affects the dependent variable by 77.9%, while the remaining 22.1% is influenced by other variables outside this research model.